Genome‐wide estrogen receptor β chromatin binding in human colon cancer cells reveals its tumor suppressor activity. Issue 3 (5th April 2021) - Indukuri, Rajitha; Jafferali, Mohammed Hakim; Song, Dandan; Damdimopoulos, Anastasios; Hases, Linnea; Zhao, Chunyan; Archer, Amena; Williams, Cecilia
Abstract: Colorectal cancer (CRC) is the third leading cause of cancer death in the western world. In women, menopausal hormone therapy has been shown to reduce CRC incidence by 20%. Studies demonstrate that estrogen activating estrogen receptor beta (ERβ) protects against CRC. ERβ is a nuclear receptor that regulates gene expression through interactions with the chromatin. This molecular mechanism is, however, not well characterized in colon. Here, we present for the first time, the cistrome of ERβ in different colon cancer cell lines. We use cell lines engineered to express ERβ, optimize and validate an ERβ antibody for chromatin‐immunoprecipitation (ChIP), and perform ChIP‐Seq. We identify key binding motifs, including ERE, AP‐1, and TCF sites, and we determine enrichment of binding to cis‐regulatory chromatin sites of genes involved in tumor development, cell migration, cell adhesion, apoptosis, and Wnt signaling pathways. We compare the corresponding cistromes of colon and breast cancer and find that they are conserved for about a third of genes, including GREB1, but that ERβ tethering to TCF and KLF family motifs is characteristic for colon. We exemplify upregulation of putative CRC tumor suppressor gene CST5 where ERβ in colon cells binds to cis‐regulatory regions nearby (−351 bp) the transcriptional start site. Our work provides a foundation for understanding the mechanism of action of ERβ in CRC prevention. Abstract : What's new? Estrogen receptor beta (ERβ) regulates gene expression through interaction with chromatin. ERβ has been shown to protect against colon cancer, and these authors set out to uncover the molecule's mechanism of action in colon cells. Using chromatin immunoprecipitation (ChIP)‐sequencing, they identified binding sites in genes involved in tumor development, cell migration, cell adhesion, apoptosis, and Wnt signaling. They identified clear differences between the chromatin binding pattern of ERβ in colon cells compared with breast cells. The results provide a map of ERβ chromatin binding sites in colon cells and position ERβ as a possible therapeutic target for colorectal cancer.